Two Warehouse Optimal Inventory Model for Non-Instantaneous Deteriorating Items - Rangarajan, K.; Karthikeyan, K. (International Journal of Engineering and Technology, 2018)
In this article, an optimal ordering policy for the stock model of items, whose deterioration starts after a certain period of time under the  dispatching policy Last in First Out (i.e. LIFO) in owned and rented warehouses is presented  with the demand of the product increases up to a certain point and that remains constant, deterioration rate which depends on time and  inflation.  The main aim of the present article is to find an optimal    inventory model, which minimizes the total stock cost. Finally, this model is analyzed through by numerical examples .